Memori dan Trauma dalam Hubungan Internasional: Pengaruh Isu “Comfort Women” terhadap Kerjasama Keamanan Jepang dan Korea Selatan - Fiandara Dwi Adityani; Hermini Susiatiningsih; Satwika Paramasatya (Journal of International Relations Diponegoro, 2018)
Japan and South Korea have a complicated relations ever since Japan’s occupation in Korean Peninsula in 1910. During Japan’s occupation, Japanese military abducted thousands of Korean women to work in a military brothel and serve as a sex slaves for Japanese forces, or known as “comfort women”. Trauma left by Japanese colonial rule created mutual animosities which hamper bilateral relations between both countries. In 2012, South Korea back off from the first military cooperation pact with Japan, due to overflow public resentment in South Korea toward Japan. The objective of this research is to understand how “comfort women” issue impacted bilateral security cooperation between Japan and South Korea. This research used qualitative methods alongside with the concept of memory, war, and world politics to explain how memory and trauma shape South Korean’s perception toward Japan, as well as the concept of Public Opinion, Domestic Structure, and Foreign Policy in Liberal Democracies to explain the impact of public opinion toward South Korea’s foreign policy. The result of this research indicated that history of “comfort women” created collective memory in South Korea, which hampers its bilateral security cooperation with Japan. The bilateral security cooperation between Japan and South Korea established only after two nations reach consensus in “comfort women” issue.